Heat Shock Protein in Cancer- A Review - M. Chandran; Ashoka Tiadi; Priyanka Singh; Gurshan Singh Gill; Nirmali Gogoi (International Journal of Pharma and Bio Sciences, 2024)
Heat shock protein (HSPs) are a highly conserved family of protein chaperones with diverse roles in cellular processes. They are categorized according to their molecular weight, and includes HSP70, HSP40, HSP27, HSP90, and HSP60. These proteins play crucial roles in folding, preventing nonspecific aggregation, and supporting proper protein function. HSPs are implicated in cancer biology, affecting the growth of tumor cells and treatment response. Unusual levels of HSPs have been linked to resistance to treatments and a worse outlook for cancer patients. Heat shock proteins could be useful in clinical settings as biomarkers for diagnosing cancer, monitoring disease progression, and serving as therapeutic targets. Understanding the complex roles of HSPs in cancer could lead to developing novel treatment strategies, including HSP-targeted therapies and immunotherapies. Further research into the precise mechanisms of HSPs in cancer progression and treatment response is essential for advancing cancer therapeutics and improving patient outcomes. This review thoroughly explores the impact of heat shock proteins, specifically HSP27, HSP40, HSP60, HSP70, and HSP90, on different cancer biology and drug research elements. The goal is to offer a detailed summary of what is currently known about the link between HSPs and cancer.